EDUCATIONAL EMPOWERMENT THROUGH ISLAMIC DIGITAL ENTREPRENEURSHIP: A STUDY ON ASNAF STUDENTS DEVELOPMENT - Basarud-din, Siti Khalilah; Nik Abdullah, Nik Safiah; Mohd Najib, Nabilah Wafa’ (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
This study examines the potential of Islamic digital entrepreneurship as a practical approach to empower Asnaf students in focusing on how Islamic entrepreneurial values align with the rapid growth of digital technology. Using a qualitative methodology grounded in an extensive literature review, the article explores the main entrepreneurs’ characteristic and educational models that are critical for cultivating digital entrepreneurial skill within this group. The findings indicate that the empowering Asnaf student in digital entrepreneurship programs and their traits. The study concludes that a deliberate integration of Islamic values into digital entrepreneurship education could play a key role in creating sustainable economic opportunities and improving the socio-economic status of Asnaf community.